Single-Shot Jones Matrix Microscopy - Gautam S.K.; Panchal P.; Mishra P.; Naik D.N.; Narayanamurthy C.S.; Singh R.K. (My University, 2025)
Field based polarization measurement is essential to understand and quantify the optical response of any target sample. The method discussed here is digital holography microscopy (Yang et al. in Opt. Express 24:25, 2016, [1]) that enables us to quantify spatially the Jones Matrix of a transparent anisotropic sample. Our method provides precise information about the polarization properties in a single shot, therefore, well suited for a dynamic biological specimen. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.